Association of Blood Biomarkers of Inflammation With Penumbra Consumption After Mechanical Thrombectomy in Patients With Acute Ischemic Stroke. (1st November 2022) - Mechtouff, Laura; Debs, Noelie; Frindel, Carole; Bani-Sadr, Alexandre; Bochaton, Thomas; Paccalet, Alexandre; Crola Da Silva, Claire; Buisson, Marielle; Amaz, Camille; Berthezene, Yves; Eker, Omer Faruk; Bouin, Morgane; et al.
Abstract : Background and Objectives: The objective of this study was to assess the relationship between blood biomarkers of inflammation and lesion growth within the penumbra in acute ischemic stroke (AIS) patients treated with mechanical thrombectomy (MT). Methods: The HIBISCUS-STROKE cohort enrolled patients admitted in the Lyon Stroke Center for an anterior circulation AIS treated with MT after brain MRI assessment. Lesion growth within the penumbra was assessed on day 6 MRI using a voxel-based nonlinear coregistration method and dichotomized into low and high according to the median value. C-reactive protein, interleukin (IL)-6, IL-8, IL-10, monocyte chemoattractant protein-1, soluble tumor necrosis factor receptor I, soluble form suppression of tumorigenicity 2 (sST2), soluble P-selectin, vascular cellular adhesion molecule-1, and matrix metalloproteinase-9 were measured in sera at 4 time points within the first 48 hours. Reperfusion was considered as successful if Thrombolysis in Cerebral Infarction score was 2b/2c/3. A multiple logistic regression model was performed to detect any association between area under the curve (AUC) of these biomarkers within the first 48 hours and a high lesion growth within the penumbra. Results: Ninety patients were included. The median lesion growth within the penumbra was 2.3 (0.7–6.2) mL. On multivariable analysis, a high sST2 AUC (OR 3.77, 95% CI 1.36–10.46), a high baseline DWI volume (OR 3.65, 95% CI 1.32–10.12), and a lack of successful reperfusion (OR 0.19, 95% CI 0.04–0.92) were associated with a high lesion growth within the penumbra. When restricting analyses to patients with successful reperfusion (n = 76), a high sST2 AUC (OR 5.03, 95% CI 1.64–15.40), a high baseline DWI volume (OR 3.74, 95% CI 1.22–11.53), and a high penumbra volume (OR 3.25, 95% CI 1.10–9.57) remained associated with a high lesion growth within the penumbra. Discussion: High sST2 levels within the first 48 hours are associated with a high lesion growth within the penumbra.